2020
DOI: 10.1093/fampra/cmaa091
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in older adults: how interprofessional teams see it? A systematic review of the qualitative research

Abstract: Background The understanding of health care providers’ experiences involved in malnutrition treatment is a key component that should be explored. Objective This systematic review aimed to explore the views and perceptions of community health care providers related to malnutrition and its management for older adults, through synthesizing the qualitative studies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The health professionals only randomly and to a lower degree provide nutritional guidance to patients with DRM. Studies found, that when health professionals in general practice identified patients as malnourished, they would refer them to a dietitian [36,47]. In this study, most of the health professionals do not have the option of using a dietitian.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The health professionals only randomly and to a lower degree provide nutritional guidance to patients with DRM. Studies found, that when health professionals in general practice identified patients as malnourished, they would refer them to a dietitian [36,47]. In this study, most of the health professionals do not have the option of using a dietitian.…”
Section: Discussionmentioning
confidence: 84%
“…Barriers mentioned in this study are consistent with barriers found in other studies [36,37], including the low recognition of malnutrition. Overwhelming workload and lack of educational opportunities and nutritional skills are mentioned in other studies as well [32,36,47,55–59]. This indicate that an intervention should include education of the health professionals [31,36,55].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While health care professionals understand the etiology of malnutrition, screening for malnutrition is not routine in many practices. 40 The Meta-Model of Interprofessional Development 21–23 theorizes that professional identity also includes perceptions on professional relevance of problem domains and determines professional engagement as well as the application of relevant professional competencies. In other words, professional identity is a meta-competence and a prerequisite of interprofessional collaboration, which guides professional contributions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other risk factors such as underlying diseases, a decreased food intake is something that can be optimized. Physicians, nurses, and dietitians tend to prescribe oral nutritional supplements as one of the first options [335,336]. The use of oral nutrition support is, in the short term, effective in increasing energy/protein intake [337] but fits not well in experienced-oriented care, is expensive [338] and does not increase life expectancy [275].…”
Section: Policy Of Food Provision In Long-term Care Facilitiesmentioning
confidence: 99%